Species screening and evaluation of live pole technique for slope stabilization in tropical environment - Mafian, Sasan (2010)
The occurrence of landslides and slope failures is common in tropical regions, particularly during the monsoon seasons. Significant numbers of slope failures in these areas have been reported on residual soil slope. Among all categories of landslide, shallow slope failures are widespread and cause costly maintenance problem. More than two-third of slope movements are shallow sliding with less than 1.5m depth. Earth slope could be stabilized using reinforcement techniques and one of these techniques which seems to be appropriate for the shallow slope failure is using Live Pole. Vegetation plays both important and wll recognized roles in improving the stability of the slopes as they can provide immediate shear strength enhancement and modify saturated soil water regime (mechanical and hydrological effects). However, the lack of proper analytic laboratory and field data for assessing and modelling the effects of live pole reinforcements in soil slope stabilities became the main objectives of this research. After reviewing related literature, the branches of eleven trees/shrubs were selected and tested for roort and stem growth in containers filled with a control media consisting of will graded sand (SW) and 10% organic matters for eight weeks and under shade-house conditions for two selected species, namely Dillenia suffructicosa (Ds) and Hibioscus tiliaceus (Ht) which were finally selected based on their root growth, diameter of root, length of root, survival rate, etc. the live poles from these two selected tree species were planted for 12 months at three slopes with five different soil types and growing/dieback rates of their plantation were investigated. In order to determine the mechanical characteristics of the stem and roots of these selected species, tests such as bending, shear and tension were conducted. These were followed by thirty-three large shear box tests on the roots and soil matrix of the live poles to determine their shear strength parameters. The results were then used in PLAXIS to analyze the stability of the planted trial slopes. The observation revealed that the safety of the slopes was significantly increased by reinforcing the effects of the live poles which is due to the higher stress concentration around the live poles. The effects of the selected live poles on the soil suction and the influence of two types of fertilizers on the growth of the live pole species were considered in the final stages of this research.